Language: Creating a Literate AEnvironment for Reading and Writing Development - Adil, I Nyoman (Lingua Scientia, 2011)
This writing provides some information about how to create a literate environment for reading and writing instruction. Hopefully, it will be useful for the general and special education teachers of kindergarten and primary level pupils. The inclusion is a discussion of those aspects of the preschooler’s rich literate environment which promote reading and writing development and specific suggestions for teacher modeling for organizing and managing the classroom, and for providing a range of meaningful reading and writing opportunities. Instruction which incorporates these suggestions is intended to extend and refine children’s written language skills acquired prior to school and to provide a transition from the informal instruction offered in the home environment to the formal instruction found in the school.